C.B. Macpherson and the problem of liberal democracy - Townshend, Jules, 1945- (Edinburgh University Press, 2000)
In this sympathetic restatement of C B Macpherson's ideas, Townshend provides an overview of Macpherson's theory of possessive individualism and critique of liberal democracy. He suggests that criticism of Macpherson has been misplaced and asks whether his theories should now be given more prominence by political theorists. This is the first book to deal comprehensively with the issues surrounding Macpherson's work; previous studies have used him as a point of departure rather than the focus of detailed analysis and none have included an overall assessment of his thought. Key Features Examination of Macpherson's project in its totality. Defence of Macpherson against his liberal, feminist, Marxist and ecological critics. Defence of his interpretation of Hobbes and Locke. Demonstration of his continuing relevance for contemporary political philosophy and for the study of politics generally.